Rice Farming Business Prospects of the M70D Variety in Praya Barat District, Lombok Central District - Marhaeny, Siti; Ansyar, Muh.; Hermawan, Yudi (Transforma Jurnal Manajemen, 2023)
This research is entitled "prospects of rice farming of the M70D variety in West Praya District, Central Lombok Regency". The objective of the research was to determine the production costs of the M70D rice farming business. To determine the income of rice farming varieties M70D. To find out the prospects for rice farming of the M70D variety. Methods This research was conducted using descriptive methods. Descriptive method is a method used to analyze problems that occur by collecting, analyzing, describing, drawing conclusions, and interpreting.The analysis used in the research includes income and feasibility analysis. The results of the analysis show that the average production cost is IDR 6,325,184 and the average income earned by farmers isRp. 5,314,816and the efficiency of rice farming of the M70D variety is 1.84. This means that rice farming is feasible to develop and it is assumed that every one rupiah spent by farmers will bring income of 0.84 rupiahs.